Evaluasi Keandalan Mesin Gilingan Tebu dengan Menggunakan Metode Reliabelity Centered Maintenance (RCM) di PG. XYZ - Setiawan, Ahmad Hari; Muttaqin, Aan Zainal; Susanto, Doni (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Industry in indonesia which is increasingly experiencing development encaurages PG.XYZ increases the realiabelity of the machine on the sugar cane milling machine, especially on the unigrator knife component, the method used in the sudy is the use the Realiabelity Centered Maintenance (RCM) methode. Data was taken during the 2023 and 2024 milling seasone, with risk analysis using FMEA Risk Priority Number the value obtained was 216 and a precentage of 17.%. Significant downtime of 1540 minutes (30%) was recorded due to the replacement of the componen. RCM analysis use the weibull distribution matrix bicause it most accurately describes the damge pattern, with an MTTF value of 588.57 hours, MTTR I hour 58 minutes. And MTBF of 225.8 hours. And for Condition derected maintenance actions, and these findings indicate the need for scheduling intervals to reduce further downtime so as to increase operational efficiency to optimally extend the life of the component.